A Facile Coating Method for Superhydrophobic Magnetic Composite Sheet from Biodegradable Durian Peel for Electromagnetic Wave Absorbance Application - Munawar, Rose Farahiyan; Arif, Afraha Baiti; Wan Abdullah Shani, Wan Nur Fateehah; Mohd Abid, Mohd Asyadi Azam; Abd Manaf, Mohd Edeerozey; Abu, Maisarah; Zainal Abidin, Muhammad Zaimi; Ismail , Syahriza (Trans tech Publication, Switzerland, 2016)
Most of the electromagnetic (EM) wave absorbers are commonly made from polymerbased materials. A large number of polymers are resistant to the environmental degradation and are thus responsible for the buildup of polymeric solid waste materials. These solid wastes cause acute environmental problems and remain undegraded for quite a long time. In a view of the awareness and concern for the problems created by the polymeric solid wastes, new biodegradable cellulosic composite with low cost and nontoxic materials, have been designed and developed. However, the properties of natural fibers that tends to absorb water, thus limiting their application. In this study,precipitated calcium carbonate (PCC) was added with stearic acid (SA) in order to generate a hydrophobic coating formulation. PCC works as filler and SA acts as surface hydrophobic modification agent. Polymer latex was then added to the coating compound as the binder. The composite surface morphology was inspected using scanning electron microscope (SEM). Results show that durian peel composite sheet had successfully achieved a superhydrophobic surface with a water contact angle of 154.85° which exceed 150°.